The family in history - Florendo, Maria Nela B. (2007)
It is without doubt that the family is an important unit of analysis in the reconstruction of the past. There is the common impression that a family history is a microhistory, which has more limitations than potentials in capturing a broad subject focus. Contrary to the view that the family is a simple social group, studies of its internal dynamics and its relations to the larger community and society show that the family ?encompasses a whole range of activities ? the political, economic, religious? (Wrigley, 1976) to name a few. McCoy?s An Anarchy of Families (1994) tackles a range of family situations and roles from the socio-economic to the political and a combination of these. Hareven (1976) posits that the family could ?provide a vantage point? to the study of societal changes over time. The said author stresses that the family is a ?constantly changing entity,? and hardly a ?monolithic institution.? Moreover, the family should not be viewed as a passive social collectivity that adapts to developments in society. Historical studies would show how families evolve as active agents of change. With this study still on its incipient phase, the paper is of two parts. The first part is a brief historiographic reflection on the family. This part includes historical research questions about the family. To lend some ?human intimacy to historical research? (Hareven 1976), the second part is an exploratory study on the history of a family (The Florendos of Vigan). It is the intention of the second part of the research to show the process of reconstructing a family history and thus make accessible to the conference participants the methodologies of history which should allow them to write their own narratives/local histories when they return to their institutions and/or communities.
Includes bibliographical references (pages 96-98).